Understanding online reading through the eyes of first and second language readers: an exploratory study - Kang, Haijun (My University, 2014)
Utilizing eye-tracking technology and focusing on the “rapid”, “purposeful” and “comprehending” attributes of fluent reading, this study investigated first language (L1) and second language (L2) readers’ online reading patterns and comprehension. Eye movement data from nine L1 readers and nine L2 readers were collected, analyzed and compared. Post-experiment interviews were conducted to obtain demographic and background information. The results indicate that L1 and L2 readers are heterogeneous when language proficiency is considered but they are homogeneous in many other aspects when the focus is on their online reading patterns and comprehension. While L1 readers read much faster than L2 readers, their attention distribution and performance on reading comprehension test are similar to L2 readers’. This study concludes that the essential online reading competency factors are similar in L1 and L2’s online reading when the “rapid”, “purposeful” and “comprehending” attributes of fluent reading are under investigation. When the core vocabulary of a language is mastered, it is metacognitive reading skills that play a major role in fluent reading in the context of new literacy.
Keywords: Online reading pattern; Online reading comprehension; Eye movement; First language reader; Second language reader